A clinical KPC-producing Klebsiella michiganensis strain carrying IncFII/IncFIA (HI1)/IncFIB (K) multiple replicon plasmid - Zhang, Na; Liu, Xiong; Qi, Lihua; Chen, Jiali; Qin, Shiyu; Jin, Meiling; Yang, Xiaojing; Liu, Fangni; Guo, Jinpeng; Liu, Jie; Wang, Changjun; Chen, Yong (Frontiers in Microbiology, 2023)
Klebsiella michiganensis is an increasingly important bacterial pathogen causing nosocomial infections in clinical patients. In this study, we described the molecular and genomic characteristics of a carbapenem-resistant K. michiganensis strain KM166 cultured from a one-month premature baby’s blood sample. KM166 showed lower biofilm forming ability in optical density (OD) than K. pneumoniae NTUH-K2044 (0.271±0.027 Vs. 0.595±0.054, P=0.001), and the median lethal dose (0.684 lg CFU/mL) was higher than K. pneumoniae strain NTUH-K2044 (6.679 lg CFU/mL). A IncFII/IncFIA(HI1)/IncFIB(K) multiple replicon plasmid in KM166 was identified carrying three replicon types. It has low homology to Escherichia coli pMRY09-581ECO_1 and the highest homology similarity to the INcFIA/INcFII(p14)-type plasmid in K. michiganensis strain fxq plasmid pB_KPC, suggesting that this multiple replicon plasmid was unlikely to had been transmitted from E. coli and probably a transfer of repFIB replicon genes from other K. michiganensis strains into the INcFIA/INcFII(p14)-type plasmid of KM166 had occurred. Mapping of the gene environment revealed that blaKPC-2 in KM166 plasmid 3 had high identity and same Tn3-tnpR-IS481-blaKPC-2-klcA_1 genomic context structure with K. pneumoniae strain JKP55, plasmid pKPC-J5501, and blaKPC-2-carrying plasmid proved to be autonomously transferred under the help of mobile genetic elements into Escherichia coli 600 by plasmid conjugation experiment. In conclusion, we have characterized a K. michiganensis strain carrying multi-replicon IncFII/IncFIA(HI1)/IncFIB(K) plasmid and blaKPC-2-carrying IncFII(p14)/IncFIA plasmid in this study, which provided insights about the evolutionary diversity of plasmids carried by K. michiganensis.